Production of polyclonal antisera of vibrio cholerae O1 & O139 to detect pathogenic vibrio cholerae - Tasnia, Rifah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.